Control of a quadrotor air vehicle by vanishing points in catadioptric images - Tarhan, Metin; Altu, Erdinc (IEEE, 2009)
Nowadays, Unmanned Air Vehicles (UAVs) have become more and more important. These vehicles are employed in many applications from military operations to civilian tasks. Under situations where global positioning system (GPS) and inertial navigation system (INS) do not function, or as an additional sensor, vision systems can be used. In recent years omnidirectional camera usage has experienced a remarkable increase. In many fields innovative research has been done by this camera which captures 360° view in a single frame. However, employment of omnidirectional cameras in UAVs is very new. In this paper, we present the use of catadioptric systems in UAVs. The parallel lines that exist on many structures in an urban environment are used by the algorithm for the estimation of the attitude of the UAV. After explanation of the algorithm, the UAV modelling and control will be presented. Various simulations have been done to present the effectiveness of the estimation algorithms as well as the UAV controllers. Finally, we will present the experiments and the results of the estimation and control algorithms on a real model helicopter.